PENGARUH MEDIA PEMBELAJARAN STEAM BERBASIS KEARIFAN LOKAL PULAU SAMOSIR TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V MIS INSAN IKHLAS ISLAMIC SCHOOL - Mei Elisa Zahra Siregar; Sujarwo; Safrida Napitupulu; Sutarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of STEAM learning media based on local wisdom of Samosir Island on the creative thinking ability of fifth grade students of MIS Insan Ikhlas Islamic School. The method used in this study is an experimental method with a Quasy Experiment type and a Non-Equivalent Control Group Design. The population of this study was all fifth grade students of MIS Insan Ikhlas Islamic School. With a total of 63 students, with class VA as the experimental class and class VB as the control. To obtain the necessary data, in this study the researcher used an instrument in the form of a test. Data analysis used the Two-Way ANOVA analysis technique, Hypothesis testing was carried out using the Analysis of Variance (ANOVA) test. After the ANOVA test, Fcount>Ftable (870.93> 4.00) was obtained, so H1 was accepted and H0 was rejected. From the results of this study, it can be concluded that there is a significant influence between STEAM learning media based on local wisdom of Samosir Island on the creative thinking ability of fifth grade students at MIS Insan Ikhlas Islamic School.